The Role of Economic Value in Shaping Repurchase Intention: Evidence from Discounts, Product Diversity, and Payment Ease with Customer Satisfaction Mediation (A Study of Awang Jaya Kepung Store) - Maulana, Satria Awang; Ayuanti, Rafikhein Novia (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the influence of discounts, product diversity, and payment convenience on repurchase intention, with customer satisfaction as an intervening variable. The research was conducted at Toko Awang Jaya Kepung, involving 143 respondents who were customers of the store. A quantitative approach with SmartPLS-based path analysis was employed to evaluate both direct and indirect effects between variables. The results revealed that discounts and product diversity have a significant positive impact on customer satisfaction, while payment convenience has a positive but not significant influence. Furthermore, discounting was found to have a significant negative impact on repurchase intention, whereas payment convenience showed a significant positive effect. In contrast, product diversity and customer satisfaction exhibited no significant direct influence on repurchase intention. Moreover, none of the independent variables demonstrated significant indirect effects on repurchase intention through customer satisfaction. These findings suggest that business strategies aimed at fostering customer loyalty should not solely rely on price promotions but must be complemented by diverse product offerings and seamless payment systems. This study provides practical insights for retail managers in similar business environments and contributes academically to the literature on consumer behavior by emphasizing the limited mediating role of satisfaction in the repurchase decision process. Future studies are encouraged to incorporate psychological constructs such as perceived value and brand trust to further explore the complexity of repurchase behavior.